2003
DOI: 10.1002/clc.4960260206
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes and prognosis in patients with hypertrophic cardiomyopathy and abnormal blood pressure responses during exercise

Abstract: SummaryBackground: An abnormal blood pressure response (BPR) during exercise has been proposed as a risk factor for sudden cardiac death in patients with hypertrophic cardiomyopathy (HCM). Some patients with HCM show systolic dysfunction during exercise.Hypothesis: The aim of this study was to clarify the hemodynamic response during exercise and prognosis in patients with HCM and abnormal BPR.Methods: Sixty-five patients with HCM underwent radionuclide monitoring of left ventricular function and measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Moreover, an abnormal blood pressure response is associated with exercise-induced LV systolic dysfunction 13 24. In addition, previous reports have suggested that peak exercise-induced systolic dysfunction in HCM represents a feature of poor prognosis 25.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, an abnormal blood pressure response is associated with exercise-induced LV systolic dysfunction 13 24. In addition, previous reports have suggested that peak exercise-induced systolic dysfunction in HCM represents a feature of poor prognosis 25.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that an abnormal blood pressure response during exercise is related to the risk of sudden death and a high prevalence of cardiac events 1113. Moreover, an abnormal blood pressure response is associated with exercise-induced LV systolic dysfunction 13 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…excessive fall in peripheral/systemic vascular resistance) 19 . It has also been suggested that lower exercise capacity and ABPR in HC may be related to diastolic dysfunction 20 and a blunted augmentation of stroke volume during exercise 21 . Although seemingly paradoxical, these mechanisms may have a single underlying and unifying aetiology related to arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal blood pressure [8][9][10] and stroke volume [9] response during exercise is a risk factor for sudden cardiac death in HCM patients. Nagata et al [11] reported that abnormal blood pressure response occurred in 11% of their patients with HCM and was associated with a high prevalence of cardiac events. Ha et al [12] reported that augmentation of left ventricular longitudinal function during exercise is blunted in HCM patients, suggesting that longitudinal functional reserve and resting longitudinal function are abnormal in these patients.…”
mentioning
confidence: 98%